The impact of lunar dust on human exploration - Levine, Joel S. (Cambridge Scholars Publishing, 2021)
When the Apollo 11 astronauts landed on the Moon on July 20, 1969, they made a very important discovery. During their landing on the surface of the Moon, the exhaust gases released from the Lunar Module landing rockets caused large amounts of surface dust to move into the thin lunar atmosphere, causing obscuration of the lunar surface. Once they landed, they found that the surface of the Moon was covered with several inches of very fine, tiny particles composed of sharp, glassy material. The lunar dust stuck to everything it came in contact with, and, once on the lunar surface, the dust eroded.